Comparative Analysis of Type IV Pilin in Desulfuromonadales - Shu, Chuanjun; Xiao, Ke; Yan, Qin; Sun, Xiao (Frontiers in Microbiology, 2016)
During anaerobic respiration, the bacteria Geobacter sulfurreducens can transfer electrons to extracellular electron accepters through its pilus. G.sulfurreducens pili have been reported to have metallic-like conductivity that is similar to doped organic semiconductors. To study the characteristics and origin of conductive pilin proteins found in the pilus structure, their genetic, structural and phylogenetic properties were analyzed. The genetic relationships, and conserved structures and sequences that were obtained were used to predict the evolution of the pilins. Homologous genes that encode conductive pilin were found using PilFind and Cluster. Sequence characteristics and protein tertiary structures were analyzed with MAFFT and QUARK, respectively. The origin of conductive pilins was explored by building a phylogenetic tree. Truncation is a characteristic of conductive pilin. The structures of truncated pilins and their accompanying proteins were found to be similar to the N-terminal and C-terminal ends of full-length pilins respectively. The emergence of the truncated pilins can probably be ascribed to the evolutionary pressure of their extracellular electron transporting function. Genes encoding truncated pilins and proteins similar to the C-terminal of full-length pilins, which contain a group of consecutive anti-parallel beta-sheets, are adjacent in bacterial genomes. According to the genetic, structure, and phylogenetic analyses performed in this study, we inferred that the truncated pilins and their accompanying proteins probably evolved from full-length pilins by gene fission through duplication, degeneration, and separation. These findings provide new insights about the molecular mechanisms involved in long-range electron transport along the conductive pili of Geobacter species.